Practical Advice for Effective Healthcare Delivery: Three Principles to Promote Quality Child Healthcare Globally - Elvira G Beracochea (Health for All Nations, 2015)
The MDGs have pointed out the large unfinished agenda of improving child health services. This short communication shows simple ways to expand and improve child health programs by improving prevention, education and early detection. The article presents a simple checklist to start improving the consistency, quality and efficiency of child healthcare delivery.